Awareness on Breast Self Examination among Reproductive Age Women - Shrestha, Sarita; Chhetri, Sharda; Napit, Jenny (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Breast self-examination (BSE) is an inspection by a woman of her breasts to detect breast problem and cancer. The objective of the study was to identify awareness on breast self-examination among the reproductive age women. Materials & Methods: A descriptive study was carried out to find out the awareness on Breast Self-Examination among Reproductive Age Group Women in Kusunti, Lalitpur. 50 women (20 to 45 years) were selected by using purposive sampling technique. Semi structured interview questionnaire was used for data collection. Results: This study showed that more than three fourth respondents (78%) said breast cancer is growth of extra lump in breast. More than three fourth respondents (82%) said diagnosis of breast cancer in early stage by BSE and only 10% of respondents had knowledge about diagnosing by mammogram. Nearly three fourth (72%) of the respondents had knowledge about meaning of BSE. More than half of the respondents (60%) got the information from health workers. One fourth of the respondents (32%) said that they don’t know about palpation in circular motion. Conclusion: Based on the findings, it is concluded women have awareness on BSE but least only know how to perform it in step wise and majority of women neglects in practicing in period basis. It is recommended that further awareness program should be conducted to fulfill the gap on BSE.